The Faunæ Ligusticæ Fragmenta of Massimiliano Spinola (1805). - Baker, Donald Burton (Contributions to Entomology = Beiträge zur Entomologie, 1999)
The Faunæ Ligusticæ Fragmenta, Decas Prima, 1805, was the first and only part to be printed of a projected work on the insects of Liguria. It was printed at the expense of its author, Massimiliano Spinola, and, so far as is known, only one copy survives, this primarily for the reason that its author shortly, and almost entirely successfully, sought to suppress it. Whether the Faunæ was or was not validly published has been disputed. It is argued here that the Faunæ was not validly published within a strict reading of the International Code of Zoological Nomenclature, and that the few taxa, all Hymenoptera, described in it should be known by the names, some altered, under which they were first validly published in the same author’s Insectorum Liguriæ, volume I, 1806. Keywords Bibliography, Italy, Insecta, Hymenoptera.